Bamboo mosaic virus mediated exogenous expression system and application thereof - WANG BAIJIE; BAO MINGCHUAN; JIN YANDONG; ZHANG HANGXIAO; ZHAO LIANGZHEN; GU LIANFENG (2023)
The invention provides a bamboo mosaic virus mediated exogenous expression system and application thereof, and belongs to the technical field of genetic engineering. Elements of the exogenous gene expression system comprise a bamboo mosaic virus genome, a pCAMBIA1302 linearized vector, an ORF5 subgenome promoter, an RNA (Ribonucleic Acid) silencing suppressor P19, a T2A self-cleavage peptide, an exogenous gene and agrobacterium GV3101. The overexpression system can be applied to moso bamboo and dendrocalamus latiflorus gene function research, and scientific guidance can be provided for bamboo molecular breeding. 本发明提供了一种竹花叶病毒介导的外源表达系统及其应用，属于基因工程技术领域。所述外源基因表达系统的元件包括竹花叶病毒基因组、pCAMBIA1302线性化载体、ORF5亚基因组启动子、RNA沉默抑制子P19、T2A自剪切肽、外源基因和农杆菌GV3101。该过表达体系能够被应用于毛竹和麻竹基因功能研究，可为竹类分子育种提供科学指导。